2015
DOI: 10.1158/2159-8290.cd-14-0971
|View full text |Cite
|
Sign up to set email alerts
|

RICTOR Amplification Defines a Novel Subset of Patients with Lung Cancer Who May Benefit from Treatment with mTORC1/2 Inhibitors

Abstract: We identified amplification of RICTOR, a key component of the mTORC2, as the sole actionable genomic alteration in an 18-year-old never smoker with lung adenocarcinoma. It occurs in 13% of lung cancers (1016 cases) in TCGA and at a similar frequency in an independent cohort of 1,070 patients identified by genomic profiling. In the latter series, 11% of cases harbored RICTOR amplification as the only relevant genomic alteration. Its oncogenic roles were suggested by decreased lung cancer cell growth both in vit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 27 publications
3
76
0
Order By: Relevance
“…Following disease progression and failure of immunotherapy, he was enrolled in a phase I clinical trial of MLN0128, another dual mTORC1/2 inhibitor, with ongoing stable disease. Reprinted with permission [43].…”
Section: Resultsmentioning
confidence: 99%
“…Following disease progression and failure of immunotherapy, he was enrolled in a phase I clinical trial of MLN0128, another dual mTORC1/2 inhibitor, with ongoing stable disease. Reprinted with permission [43].…”
Section: Resultsmentioning
confidence: 99%
“…Like RAC and TRIO, RICTOR has been implicated in several cancers (4144). A tumor-specific function of RICTOR was demonstrated in studies using knockout mice; RICTOR was shown to be dispensable for normal prostate development but essential for the development of PTEN-loss-induced prostate cancer (41).…”
Section: Discussionmentioning
confidence: 99%
“…RICTOR gene amplification and Rictor overexpression was noted in a subset of lung cancer patients with susceptibility to mTORC1/2 dual kinase inhibitors(20). Rictor overexpression was also reported in melanomas(21), glioblastomas (22, 23), gastric cancers(24), and hepatocellular carcinomas(25), supporting a potential role for mTORC2 components in aggressive tumors, and highlighting Rictor/mTORC2 as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%